Mono No Aware Dalam Manga Koizora Karya Ibuki Haneda - Kumala Dewi, Anak Agung Istri; Ari Sulatri, Ni Luh Putu; Damayanti, Silvia (Humanis; Volume 17. No. 1. Oktober 2016, 2017)
This research en titled "mono no aware in manga koizora written by Ibuki Haneda". The main purpose of this research is to discover the sadness value of mono no aware and the attitude of the characters in dealing with mono no aware. Several theories that are used  in this research include literature psychology theory proposed by Freud (2008) and semiotics theory proposed by Danesi (2010). The used method to analyse data in the research is descriptive method. The result of this research indicates that the value of mono no aware which is included in the manga encompasses 1) sadness; 2) regret; and 3) compassion,. The attitudes shown by the characters in dealing with mono no aware are sincere, 1) accepting the fate; 2) live with the fate; 3) do not dissolved in sadness; 4) emphaty; 5) support; 6) inspire; 7) care; 8) anger; and 9) calm.
Keywords: mono no aware, social psychology, attitude character